Electrothermal silver nanowire thin films for In-Situ observation of thermally-driven chemical processes - Martínez, Eduardo David (2018)
We develop a novel device comprised of high optical transmittance thin films containing silver nanowires (AgNWs) in poly(methyl methacrylate) (PMMA) acting as heating elements. The electrothermal control of the AgNWs network allows us to externally trigger and tune the temperature conditions required to run chemical reactions and physicochemical processes. The device was successfully applied for the spectroscopic in-situ observation of three different model reactions: i) the thermal equilibrium of a CoCl2/HCl/H2O complex, ii) the reversible macromolecular phase transition of a pNIPAM solution, and iii) the nucleation and growth of gold nanoparticles (AuNPs). In the first case, the color of the Co2+ complex was reversibly switched from pink to blue when changing the thermal equilibrium condition. In the second one, the optical transmittance of an aqueous solution of carboxylic-terminated pNIPAM polymer was cycled from high to low as the temperature of the solution was below or above the lower critical solubility temperature (LCST) respectively. Finally, the electrothermal control on the device was applied to the study of the nucleation and growth of AuNPs in an organic solution of AuCl3 containing oleylamine acting as both the reducer and the stabilizing agent. The versatility of the electrothermal device provides an easy way to undertake thermally controlled processes and develop optical elements such as smart windows and lab-on-a-chip devices. The AgNWs-PMMA nanocomposite was also applied successfully as an electrothermal ink on the external side walls of a test tube.